2014
DOI: 10.1016/j.colsurfa.2014.05.048
|View full text |Cite
|
Sign up to set email alerts
|

Tuneable surface modification of PLGA nanoparticles carrying new antitubercular drug candidate

Abstract: Biodegradable poly(lactic-co-glycolic acid)(PLGA 50:50) nanoparticles (NPs) were prepared and characterized in terms of size, composition, zeta potential and colloidal stability. Surface modification of PLGA NPs where primary amino groups were introduced to the Pluronic surface layer was developed. This method allows modulation of the charge character of the nanoparticle surface and provides functional groups for chemical reactions useful for targeting while retaining the aggregation stability of the system. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 40 publications
4
19
0
1
Order By: Relevance
“…Therefore we may expect that NPs containing Pluronic-amine surface layer show higher cellular uptake rate. This assumption was supported by our experimental data on drug loaded PLGA NPs [48]. When the carriers were functionalized by Pluronic F127 and Pluronic-F127-amine highly increased in vitro efficiency was achieved for an antituberculotic drug candidate.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Therefore we may expect that NPs containing Pluronic-amine surface layer show higher cellular uptake rate. This assumption was supported by our experimental data on drug loaded PLGA NPs [48]. When the carriers were functionalized by Pluronic F127 and Pluronic-F127-amine highly increased in vitro efficiency was achieved for an antituberculotic drug candidate.…”
Section: Discussionsupporting
confidence: 77%
“…When the Pluronic-amine derivative was used for the stabilization of the particles increased internalization and intracellular antibacterial effect was obtained. The presence of cationic charges on the particle surface was shown to increase the non-specific cell membrane affinity of the particles leading to increased cellular uptake rate [48].…”
Section: Discussionmentioning
confidence: 99%
“…Mesoporous silica particles functionalised with polyethyleneimine or with a pH‐responsive nanovalve were used for delivery of RF and isoniazid, respectively . Polymeric nano‐ and microparticles containing RF and other drugs, with or without surface modification, have also shown to be taken up into macrophages …”
Section: Introductionmentioning
confidence: 99%
“…However, it was found that the hydrophobic character of the PLGA causes the nonspecific adsorption of plasma proteins directing to the uptake of the particles by the mononuclear phagocyte system and therefore their fast clearance from the body. It is recognized that this problem can be prevented if the particles are surface modified by the adsorption or grafting of hydrophilic polymers such as polyethylene glycol (PEG) or poly(ethylene oxide) (PEO) to improve its surface biocompatibility [83,84]. In 2016, Gyulai et al [83] with the aim to increase the potential of targeted drug delivery synthesized the end group derivative of Pluronics a promising drug carrier systems.…”
Section: Application Of Biodegradable Nanostructure Polymersmentioning
confidence: 99%